Tindak Pidana Pencucian Uang (TPPU): Analisis Yuridis terhadap Peran Korporasi dalam Kejahatan Keuangan - Wijayanti, Fatimah Ratna; Zulfkifi, Effi; Pasaribu, August H. (Postulat, 2025)
Money laundering poses a global threat to the integrity of financial systems, and corporations often play a central role in this crime. This research aims to juridically analyze the role of corporations in money laundering in Indonesia, focusing on the prevailing legal framework and challenges in its enforcement. The research method employed is qualitative normative law, analyzing Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering and relevant literature. The results indicate that although Indonesian law recognizes corporate criminal liability in money laundering cases, there are significant challenges in its implementation and enforcement. This study concludes that there is a need for regulatory strengthening, enhanced oversight, and closer inter-agency cooperation to combat money laundering involving corporations more effectively.